Presencia del virus de Leucemia Felina en el Cantón Baba. - Intriago Palacios, Gabriela Estefanía (2023)
FeLV is a virus that affects domestic and wild cats worldwide. Its diagnosis can be made through tests such as ELISA and Immunochromatography. Early diagnosis and timely treatment improve the quality of life of the cat. In the urban area of the Baba canton, Los Ríos province, in the sectors, Barrio Cuba, Las Malvinas and Baba Central, research was carried out with the objectives of identifying the virus antibody through immunoassay, relating the risk factors that influence the presence of the disease and analyzing its presence in domestic cats with and without symptoms, to know the current situation of ViLeF in the canton, since there is no previous study on the subject. After conducting a test on 50 cats, it was discovered that 46% (23 cats) were positive for FeLV, while 54% were negative (27 cats). The majority of positive cases were unneutered males and cats between 1 and 2 years old, making them more vulnerable to contagion due to fights or mating with other felines. In conclusion, it is important to prevent contagion in healthy cats through isolation of sick animals and vaccination. It is recommended to follow a vaccination protocol to prevent infection. This protocol may include vaccines against these viruses at regular intervals according to the veterinarian’s recommendations